2016
DOI: 10.1007/s00401-016-1553-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of glial-specific Kir4.1 in normal and pathological states of the CNS

Abstract: Kir4.1 is an inwardly rectifying K(+) channel expressed exclusively in glial cells in the central nervous system. In glia, Kir4.1 is implicated in several functions including extracellular K(+) homeostasis, maintenance of astrocyte resting membrane potential, cell volume regulation, and facilitation of glutamate uptake. Knockout of Kir4.1 in rodent models leads to severe neurological deficits, including ataxia, seizures, sensorineural deafness, and early postnatal death. Accumulating evidence indicates that Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
182
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(194 citation statements)
references
References 130 publications
(223 reference statements)
10
182
1
1
Order By: Relevance
“…The presence of several presynaptic markers at the plaque‐associated dystrophies (this work, Sanchez‐Varo et al, 2012, Trujillo‐Estrada et al, 2014) strongly suggests the presynaptic nature of these pathological structures. Similar findings have been also reported in another APP/PS1 model (Sadleir et al, 2016). However, we cannot rule out the possibility that some of these dystrophies are in fact axonal portions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of several presynaptic markers at the plaque‐associated dystrophies (this work, Sanchez‐Varo et al, 2012, Trujillo‐Estrada et al, 2014) strongly suggests the presynaptic nature of these pathological structures. Similar findings have been also reported in another APP/PS1 model (Sadleir et al, 2016). However, we cannot rule out the possibility that some of these dystrophies are in fact axonal portions.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, transcellular degradation of neuronal dystrophies by astrocytes might directly support neuron survival or, alternatively, it might reduce the Aβ release from dystrophic presynaptic elements. In this sense, presynaptic dystrophies are sites of APP accumulation and putative Aβ release (Sanchez‐Varo et al, 2012; Torres et al, 2012) and, as recent studies indicate, the accumulation of BACE1 in presynaptic dystrophies surrounding plaques causes increased cleavage of APP and Aβ generation, which could lead to an exacerbation of amyloid pathology in AD (Sadleir et al, 2016; Torres et al, 2012). Alternatively, insulating dystrophies from the normal tissue might also decrease the probability of possible adverse inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both human postmortem tissue and animal models of seizure show reactive astrocytes, which exhibit increased expression of the intermediate filament glial fibrillary acidic protein (GFAP) and alteration of astrocyte channels, including the water channel aquaporin-4 (AQP4) and the inward rectifying potassium channel Kir4.1, both of which are central to epileptogenesis (Oberheim et al, 2008; Anderson and Rodriguez, 2011; Binder et al, 2012; de Lanerolle et al, 2012; Rodriguez-Cruces and Concha, 2015; Nwaobi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The reduced expression or dysfunction of Kir4.1 channels seems to be involved in several diseases (Loudon and Fry, 2014; Nwaobi et al, 2016). Recent studies showed that loss-of-function mutations of the human gene ( KCNJ10 ) encoding Kir4.1 channels are responsible for the SeSAME/EAST syndrome, an autosomal recessive disorder characterized by seizures, sensorineural deafness, ataxia, intellectual disability and electrolyte imbalance (Bockenhauer et al, 2009; Scholl et al, 2009; Reichold et al, 2010).…”
Section: Introductionmentioning
confidence: 99%